MODEL PENDUGAAN KONSUMSI KAYU LAPIS OLEH RUMAH TANGGA DI DAERAH JAWA TENGAH DAN JAWA TIMUR - Rachman Effendi; Buhannan Buhannan (Jurnal Penelitian Hasil Hutan, 1989)
The  development  of  domestic   market  of  plywood  relies  heavily  on  the effective   demand  for plywood  or buying  power   in  real sense.                                                                                                               This  research is aimed  at studying   the pattern   of  relation  ship  between   the  consumption  of plywod  by household in Central  Java  and  East  Java  and  some  factors  influencing  it.The  average volume  of plywood  annually  consumed   by household   is of 0.0152  m3 per year per  family   (with  average of  3. 6 persons/family).   The  variables  that  influence  the effective  demand  of plywood are family  income,  price  of plywood and  the  number   of  family   member.    The  elasticity   of  the  demand   of  the  three  factors  is  of  0.3365  implying   that  the consumption of plywood  is inelastic  to the change of  the three factors.